2023
DOI: 10.3390/app13031230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Printing Parameters on Mechanical Performance of Material-Extrusion 3D-Printed PEEK Specimens at the Point-of-Care

Abstract: Additive manufacturing (AM) of polyetheretherketone (PEEK) biomaterials using the material-extrusion (MEX) method has been studied for years. Because of the challenging manufacturing process, precisely controlling printing parameters is crucial. This study aimed to investigate the effects of printing parameters such as orientation and position of printing on mechanical properties. Thus, 34 samples were printed using PEEK filament and the MEX process. Samples were divided into two main groups (A,B) according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Considering the mechanical properties of the massive material, PEKK appears to be closer to bone; nonetheless, it should be considered that bone substitutes should be produced as porous materials to promote osteointegration [ 52 ]. Furthermore, other authors analyzing similar specimens, with the same printing orientation but using 3D-printed PEEK found an elastic modulus equal to 1.64 GPa at the same raster angle (±45°) [ 56 ]. It is therefore possible to conclude that PEKK is stiffer than PEEK.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the mechanical properties of the massive material, PEKK appears to be closer to bone; nonetheless, it should be considered that bone substitutes should be produced as porous materials to promote osteointegration [ 52 ]. Furthermore, other authors analyzing similar specimens, with the same printing orientation but using 3D-printed PEEK found an elastic modulus equal to 1.64 GPa at the same raster angle (±45°) [ 56 ]. It is therefore possible to conclude that PEKK is stiffer than PEEK.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, PEKK material could be more suitable also from the point of view of the elastic modulus unless a different raster angle is chosen. It should be considered that when using PEEK, moving from a raster angle of ±45° to 0° or 90°, the elastic modulus can vary from 1.64 GPa [ 56 ] to 3.79 GPa [ 57 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2023) studied to find out the optimal parameter settings that lead to improved mechanical properties, taking into consideration factors such as print resolution and print time. They also discussed the effect of printing parameters on the microstructure and surface quality of the printed specimens [32]. Further, Marianna et al (2023) studied that the adding nanofillers to the PEEK matrix enhances the mechanical properties of 3D printed nanocomposites, improving stiffness, strength, and toughness, also they found in agreement between analytical models and experimental results that suggests the model's efficacy in predicting the mechanical behaviour of the nanocomposites [33].…”
Section: Fig1: Schematic View Of (Filament Fused Fabrication) 3d Peek...mentioning
confidence: 96%
“…PEEK, a semi-crystalline polymer, exhibits favorable characteristics, including biocompatibility, mechanical strength, durability, lightweight, dimensional stability, and low affinity for plaque accumulation. These properties make PEEK a promising alternative material for manufacturing space maintainers [33,[69][70][71][72]. Furthermore, a study conducted in 2020 demonstrated the high suitability of removable PEEK space maintainers for clinical applications.…”
Section: • Millingmentioning
confidence: 99%